1992
DOI: 10.1007/bf00219337
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative correlation between the residual activity of β-hexosaminidase A and arylsulfatase A and the severity of the resulting lysosomal storage disease

Abstract: A previously suggested model for the correlation between residual activity of a lysosomal enzyme and the turnover rate of its substrate(s) has been extended to a discussion of substrate accumulation rates in individual cells and whole organs. With these considerations, much of the observed variability in age of onset and clinical phenotype, as well as the phenomenon of pseudo-deficiency, can be understood as the consequences of small differences in the residual activity of the affected enzyme. In order to expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
177
0
5

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(197 citation statements)
references
References 35 publications
15
177
0
5
Order By: Relevance
“…In humans, a residual ASA activity of 5-10% of normal prevents the manifestation of MLD, and thus it was supposed that similar levels might be therapeutically effective in mice. 15,16 The finding that unexpectedly high amounts of ASA have to be substituted for correction of sulfatide storage may be due to several reasons. Low amounts of residual enzyme activity are sufficient to prevent storage in normal equilibrium conditions, in which sulfatide does not accumulate.…”
Section: Figure 4 Cross-sectional Areas Of Axons Of Myelinated Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, a residual ASA activity of 5-10% of normal prevents the manifestation of MLD, and thus it was supposed that similar levels might be therapeutically effective in mice. 15,16 The finding that unexpectedly high amounts of ASA have to be substituted for correction of sulfatide storage may be due to several reasons. Low amounts of residual enzyme activity are sufficient to prevent storage in normal equilibrium conditions, in which sulfatide does not accumulate.…”
Section: Figure 4 Cross-sectional Areas Of Axons Of Myelinated Fibersmentioning
confidence: 99%
“…This value exceeds the enzyme activity levels which are sufficient to prevent the manifestation of MLD. 15,16 The enzyme levels in serum correlated with the amount of enzyme found in the kidney and liver, suggesting that endocytosis determines the amount of ASA delivered to these tissues. There was no correlation of serum ASA levels with the amount of enzyme found in the brain, which demonstrated that delivery to the brain is not due to endocytosis, but possibly due to bone marrow-derived cells migrating into the brain, which depending on the proviral integration site may express more or less ASA after microglial differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in SGSH activity in the fibroblasts of SP patients was up to 43% of the lower limit of normal activity. Previous studies of other lysosomal enzymes, including glucosylceramide β‐glucosidase and β‐hexosaminidase A, did show that 10 to 15% of the residual lysosomal enzyme activity prevented the accumulation of metabolites 29, 30. This, in combination with the observation that HS levels even normalized in some fibroblast cell lines at 30 °C, suggests that this effect might be of clinical relevance if the same effect were induced, for example, by pharmacological chaperones.…”
Section: Discussionmentioning
confidence: 84%
“…Accumulation of undegraded substrate occurs only when the residual activity is below the critical threshold of 10-15% of normal enzyme activity. 60 Depending on the nature of the defective enzyme and the type and site of the mutation, there may be great differences in the age of onset, severity of the manifestations, and organ involvement for each lysosomal storage disease. Furthermore, since the genetic defect, whether it be deficient enzyme activity, abnormal en- zyme targeting, or impaired product efflux, etc., occurs in all cell types of affected individuals, the amount of abnormal storage in specific cells is determined by the type and amount of available substrates that are recycled in these cells.…”
Section: Morphological Biochemical and Molecular Biology Approaches mentioning
confidence: 99%